2020
DOI: 10.1152/jn.00391.2019
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of the supplementary motor area on primary motor cortex outputs

Abstract: Premotor areas of primates are specialized cortical regions that can contribute to hand movements by modulating the outputs of the primary motor cortex (M1). The goal of the present work was to study how the supplementary motor area (SMA) located within the same hemisphere [i.e., ipsilateral SMA (iSMA)] or the opposite hemisphere [i.e., contralateral (cSMA)] modulate the outputs of M1. We used paired-pulse protocols with intracortical stimulations in sedated capuchin monkeys. A conditioning stimulus in iSMA or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Based on this analysis, it appears that order in which data was collected across cortical sites within an animal does not affect the pattern of modulation. This finding is in line with the lack of cumulative effects we have previously found when using similar protocols in both rats (Deffeyes et al 2015) and monkeys (Côté et al 2017(Côté et al , 2020Quessy et al 2016).…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…Based on this analysis, it appears that order in which data was collected across cortical sites within an animal does not affect the pattern of modulation. This finding is in line with the lack of cumulative effects we have previously found when using similar protocols in both rats (Deffeyes et al 2015) and monkeys (Côté et al 2017(Côté et al , 2020Quessy et al 2016).…”
Section: Methodssupporting
confidence: 91%
“…To date, studies on interhemispheric interactions in humans or NHPs have focused on the modulatory effects of premotor areas on M1 outputs (Buch et al 2010;Côté et al 2017;Fiori et al 2017;Koch et al 2007;Mochizuki et al 2004aMochizuki et al , 2004bQuessy et al 2016). In NHPs, we have compared the pattern of modulation from various premotor areas on M1 outputs using very similar techniques as the ones in the present study (Côté et al 2017(Côté et al , 2020Quessy et al 2016). Much like RFA in rats, premotor areas induce strong modulations that are affected by the timing of stimulations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, SMA-M1 connectivity ratios at each ISI varied to some extent both between and within individuals, suggesting that a conditioning stimulus to SMA can have both an inhibitory and a facilitatory influence on M1 excitability. A nonhuman primate study using pairedpulse electrical stimulation to investigate connectivity between ipsilateral SMA and M1 showed that stimulating SMA facilitated M1 excitability at short ISIs (1, 2, 2.5 and 5 ms) but inhibited M1 excitability at longer ISIs (10 and 20 ms) (Cote et al, 2020). This finding, suggesting that facilitatory and inhibitory influences of SMA on M1 are time-dependent in nonhuman primates, fits with dualsite TMS studies in humans showing a facilitatory effect of SMA on M1 at short ISIs (6, 7 and 8 ms) but an inhibitory effect of SMA on M1 at a longer ISI (40 ms) in younger adults (Arai et al, 2011(Arai et al, , 2012Fiori et al, 2017;Green et al, 2018).…”
Section: Intra-individual and Interindividual Variability In Sma-m1 Connectivitymentioning
confidence: 99%